A FDEM based 3D discrete mixed seepage model for simulating fluid driven fracturing. (July 2022) - Yan, Chengzeng; Gao, Yakun; Guo, Hui
Abstract: This paper presents a 3D discrete mixed seepage model that considers the effect of fracture on pore seepage. We unify the 3D fracture-pore mixed seepage model and finite-discrete element method (FDEM) to build a coupled hydro-mechanical model to simulate the fluid-driven deformation and fracturing, which can also consider the influence of fracture propagation on fracture seepage and pore seepage. The model has been implemented in a GPU parallel multiphysics finite-discrete element software MultiFracS. For the continuum seepage problem, we conduct a parameter sensitivity analysis for the fluid exchange coefficient and propose the criterion for selecting the coefficient. Then, we verify the model to deal with 3D pore seepage in a continuum media, fracture-pore seepage in discontinuous media with a single fracture, and fracture-pore seepage in discontinuous media with multi-fractures. Finally, the coupled hydro-mechanical model is employed to study a one-dimensional consolidation and a hydraulic fracturing problem. The research shows that the simulation results are in good agreement with the analytical solutions and the experimental results, which verifies the effectiveness of the method for solving the 3D fracture-pore mixed seepage and the coupled hydro-mechanical model for dealing with seepage problems in fractured porous media and fluid-driven fracturing.